Exploring the antecedents of intention towards adoption of internet banking: a study in rural setting. (16th January 2020) - Tyagi, Shagun
Through this research an attempt has been made to analyse the impact of factors influencing the consumer intentions to adopt e-banking services in rural areas. For this purpose, a cross-sectional study was conducted. The study was conducted on 409 respondents. Trust, internet banking awareness, perceived ease of use, financial literacy and perceived risk were used as predictors of consumer intentions to adopt internet banking. A structural model was generated by applying SEM through AMOS. The results of the study show that trust is a strong predictor of the consumer intentions and consumer information privacy is not just necessary but mandatory for building a level of trust. The researchers also conclude that perceived risk needs to be extended in future studies so that its relationship with use of perceived ease can be explained in a better way and explaining the effect of financial literacy on consumer intention to adopt online service.